EMPATHY AND SOCIAL INTELIGENCE - Meşküre Hülya Ünal-KARAGÜVEN (Fırat University, 2019)
This is a review of literature study about empathy and social intelligence. Additionally, the relationship between empathy and social intelligence is briefly reviewed. Contemporary education needs eligible teachers in order to teach or transfer knowledge. Additional, teachers should have knowledge and skills about empathy and social intelligence. Empathy means the ability to feel and share another person’s emotions. Teachers can increase the efficiency of education by learning more about empathy and social intelligence. They should be good models for their students with empathic and social behaviors. There are many studies on empathy and social intelligence in recent years. The purpose of this study to present of a summary about empathy and social intelligence. At the first part of the study; empathy and the measurement of empathy, at the second part of the study; social intelligence and relationship between empathy and social intelligence, at the third part of the study; why and how the empathy and social intelligence should be developed, are studied. In the last part of the study, some examples about the activities are given. In summary, this study can be a resource for educators and researchers. To gain a greater understanding of the empathy, subsequent studies of empathy should involve not only social intelligence but also different types of factors. Thus, replication attempts about the empathy should include various subjects.